Gender and MSMEs in the food environment in Viet Nam - Berg, Marrit van den (International Food Policy Research Institute, 2023)
Despite the introduction of supermarkets, Vietnam’s food retail market is still dominated by wet markets, informal street markets and mobile vendors. These are less expensive than supermarkets and offer various other advantages, such as the opportunity to purchase food on in formal credit from the vendor, discounts in the evening, and additional services such as cutting vegetables and delivery. As a result, supermarkets and convenience stores are of limited importance for food consumption of low-income households in Hanoi. Yet even many wealthier people still do at least part of their food shopping at small traditional sellers. Many informal vendors are migrants from rural areas, who often lack the formal education and social capital to gain formal employment. Previous research has shown stark differences between male and female retailers in informal food markets in Vietnam. In the informal system, women tend to operate based on social relations rather than economic interactions, contrasting men’s activities that tend to be more capital-based and similar to the formal system. However, no recent quantitative information is avail able on the representation of men and women in the various types of food outlets in Vietnam